Data warehouse structuring methodologies for efficient mining of Western Australian petroleum data sources - Nimmagadda, Shastri; Dreher, Heinz; Rudra, Amit (IEEE, 2005)
Representing the knowledge domain of a petroleum system is a complex problem. In the present study, logical modelling of shared attributes of resources industry entities (dimensions or objects) has been used for construction of a dynamic and time-variant metadata model. This work demonstrates effectiveness of multidimensional data modelling for petroleum industry, which will be further investigated for fine-grain data presentation and interpretation for quality knowledge discovery.